"Absence makes the heart grow fonder": A qualitative examination of sibling relationships during emerging adulthood. (August 2019) - Hamwey, Meghan K.; Rolan, Emily P.; Jensen, Alexander C.; Whiteman, Shawn D.
The present study explored the unique experiences of siblings during emerging adulthood. Using a qualitative design, this study sought to better understand sibling relationship dynamics (e.g., closeness and negativity), communication strategies (e.g., frequency, quality, and form), and the implications of siblings' proximity with one another. Importantly, the period of emerging adulthood provides a unique context in which these experiences might be especially salient. We posited the following research questions: What do sibling relationships look like during emerging adulthood? What does communication look like between siblings during emerging adulthood and how does it impact their relationship? and What implications does proximity have for the sibling relationship? To answer these questions, nine different qualitative focus groups ( N = 45 participants) were conducted across two different university settings. Results suggested that siblings remained important in the lives of emerging adults, despite a lack of physical proximity and less frequent communication. Participants indicated that although communication was less frequent, the content of the discussions was often more meaningful. When sharing in-person conversations, participants described the relationships to have picked up where they had left off, with no time passing in between. Further, sibling relationship quality appeared to improve with participants, indicating they were happier with their sibling and felt more like equals and had a better understanding of one another. These findings help to fill a gap in knowledge about sibling relationships during emerging adulthood and elucidate our understanding of how these relationships are maintained and developed during this period of transition.